PELATIHAN SISTEM PEMBELAJARAN JARAK JAUH (PJJ) MENGGUNAKAN GOOGLE CLASSROOM PADA GURU SMAN 1 TANJUNG SARI, LAMPUNG SELATAN - Putra, Endo Pebri Dani; Lisdayana, Nurmalisa; Nugraha, Aditya Wahyu; Maslami, Vebera; Praseptiawan, Mugi (TeknoKreatif: Jurnal Pengabdian kepada Masyarakat, 2023)
Google Classroom is a new platform, so there needs to be training for institutions or institutions that are new to using this platform. SMAN 1 Tanjung Sari is one of the schools that requires training in using google classroom to run the online learning process. The purpose of this training is to improve the knowledge and skills of teachers and students in conducting online learning using the google classroom platform. Learning system training through Google Classroom is carried out by conducting surveys first and preparing questionnaires before and after the training. The results of the training implementation increased participants' knowledge and skills in using google classroom from before the training, which was 0% to 100%, and increased participants' knowledge of using the google classroom platform from 20% to 100%. Therefore, it can be concluded that online learning training using google classroom is very important to do in increasing knowledge and skills so that the learning objectives of the school or institution are achieved.